Dinámica de los herbicidas en el suelo - Campi Goyes, Julio Humberto (2023)
Herbicides are essential for increasing agricultural productivity, but present environmental and health challenges. This research emphasizes understanding their interaction in the soil and conserving soil as a key resource for sustainable agriculture, addressing water pollution and resistance in weeds by characterizing herbicide dynamics. The research focuses on understanding the dynamics of herbicides in the soil to minimize their environmental impact and improve their effectiveness in weed control. Specific objectives address half-life, degradation, influence on soil biodiversity and weed resistance. The theoretical framework provides information on weed types, their impact on agriculture and herbicide composition. The results show that soil organic amendments diversely affect herbicide dynamics, with organic carbon increasing its persistence in the superficial layers and chemical oxygen demand (COD) increasing its release in deeper layers. Furthermore, the degradation of herbicides such as 2,4-D and MCPA is mainly microbial in rice cultivation soils, reducing groundwater contamination, although herbicides such as glyphosate negatively affect the soil microbiota and beneficial organisms such as earthworms. , which can impact soil health and nutrient availability.